Visualizing Synaptic Multi-Protein Patterns of Neuronal Tissue With DNA-Assisted Single-Molecule Localization Microscopy - Narayanasamy, Kaarjel K.; Stojic, Aleksandar; Li, Yunqing; Sass, Steffen; Hesse, Marina R.; Deussner-Helfmann, Nina S.; Dietz, Marina S.; Kuner, Thomas; Klevanski, Maja; Heilemann, Mike (Frontiers in Synaptic Neuroscience, 2021)
The development of super-resolution microscopy (SRM) has widened our understanding of biomolecular structure and function in biological materials. Imaging multiple targets within a single area would elucidate their spatial localization relative to the cell matrix and neighboring biomolecules, revealing multi-protein macromolecular structures and their functional co-dependencies. SRM methods are, however, limited to the number of suitable fluorophores that can be imaged during a single acquisition as well as the loss of antigens during antibody washing and restaining for organic dye multiplexing. We report the visualization of multiple protein targets within the pre- and postsynapse in 350 - 400 nm thick neuronal tissue sections using DNA-assisted single-molecule localization microscopy. In a single labeling step, antibodies conjugated with short DNA oligonucleotides visualized multiple targets by sequential exchange of fluorophore-labeled complementary oligonucleotides present in the imaging buffer. This approach avoids potential effects on structural integrity when using multiple rounds of immunolabeling and eliminates chromatic aberration, because all targets are imaged using a single excitation laser wavelength. This method proved robust for multi-target imaging in semi-thin tissue sections with a lateral resolution better than 25 nm, paving the way towards structural cell biology with single-molecule super-resolution microscopy.